2017
DOI: 10.7324/jabb.2017.50101
|View full text |Cite
|
Sign up to set email alerts
|

Screening, Selection and Optimization of the Culture Conditions for Tannase Production by Endophytic Fungi Isolated from Caatinga

Abstract: Tannin acyl hydrolase (EC 3.1.1.20), called tannase, is an enzyme of great biotechnological interest for applications in food, chemical, beverage and pharmaceutical industries. Therefore, the objective of this study was to isolate, select and identify strains of endophytic fungi from rich tannin plants collected in the Caatinga, as well as, the optimization of culture conditions for the best producers. Sixteen endophyte fungi were isolated from the barks of mastic (Myracrodruon urundeuva Allemão), angico (Anad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…The tannase activities show a high correlation with r= 0.9204 between the hydrolytic zone diameter and tannase activity in all 13 fungal isolates. These results are in line with previous studies [10], [23], [24]. Their studies showed a correlation between tannase activity and the diameter of hydrolytic zone produced by isolates on plate assay.…”
Section: B Secondary Screening Under Submerged Fermentationsupporting
confidence: 93%
“…The tannase activities show a high correlation with r= 0.9204 between the hydrolytic zone diameter and tannase activity in all 13 fungal isolates. These results are in line with previous studies [10], [23], [24]. Their studies showed a correlation between tannase activity and the diameter of hydrolytic zone produced by isolates on plate assay.…”
Section: B Secondary Screening Under Submerged Fermentationsupporting
confidence: 93%
“…The endophytic fungus Aspergillus fumigatus CAS21 was isolated from the bark of the cashew tree ( Anacardium occidentale L.) ( Cavalcanti et al, 2017 ) and stored in the Laboratory of Microbiology of the Faculdade de Filosofia, Ciências e Letras de Ribeirão Preto, University of São Paulo, Brazil. The fungus was maintained on potato dextrose agar (PDA) slants at 37°C for 96 h and then stored at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The fungus was maintained on potato dextrose agar (PDA) slants at 37 °C for 96 h and then stored at 4 °C. The liquid cultures were obtained by means of the inoculation of 1 ml of spore suspension (10 5 spores/ ml) of the A. fumigatus CAS21 in 25 ml of mineral medium containing 0.1% (w/v) peptone and 2% (w/v) tannic acid as additional carbon source (Cavalcanti et al, 2017). The culture medium was previously autoclaved at 120 °C and 1.5 atm for 20 min, and the tannic acid was sterilized by microfiltration using a syringe filter (0.22 μm) before the addition to the medium.…”
Section: Microorganism and Culture Conditionsmentioning
confidence: 99%
“…The endophytic fungus Aspergillus fumigatus CAS21 was isolated from the bark of the cashew tree (Anacardium occidentale L.) (Cavalcanti et al 2017) and stored in the Laboratory of Microbiology of the Faculdade de Filosofia, Ciências e Letras de Ribeirão Preto at the University of São Paulo, Brazil. The fungus was maintained on Potato Dextrose Agar (PDA) slants at 37 ºC for 96 h and then stored at 4 ºC.…”
Section: Microorganismmentioning
confidence: 99%
“…Submerged cultures (SbmF) were obtained with the inoculation of 1-mL spore suspension (10 5 spores mL −1 ) of the Aspergillus in a medium containing 0.1% (w/v) KH 2 PO 4 , 0.2% (w/v) MgSO 4 •7H 2 O, 0.1% (w/v) CaCl 2 , 0.3% (w/v) NH 4 Cl, and 0.1% (w/v) peptone, and 2% (w/v) tannic acid as additional carbon source. The culture medium was previously autoclaved at 120 °C and 1.5 atm for 20 min, and the tannic acid was sterilized by means of microfiltration using a syringe filter (0.22 μm) before being added to the medium (Cavalcanti et al 2017). The cultures were kept at 37 °C for 24 h and shaking at 120 rpm.…”
Section: Tannase Productionmentioning
confidence: 99%